Book Review His Majesty’s Headhunters: The Siege of Kohima that shaped World History by Mmhonlumo Kikon - Yhome, Lucy Keneikhrienuo (SARE: Southeast Asian Review of English, 2025)
Mmhonlumo Kikon’s His Majesty’s Headhunters: The Siege of Kohima that Shaped World History (2023) is a significant addition to the historiography of Northeast India, particularly in the context of colonialism and World War II. The book challenges dominant historical narratives by centering the agency of the Naga people in both resisting British imperialism and playing a decisive role in the Battle of Kohima. Through a combination of archival research and oral histories, Kikon reclaims the Indigenous perspective, offering a counter-narrative to colonial accounts that have long marginalized Naga voices. This review critically engages with Kikon’s methodological interventions, his argument on the erasure of Naga contributions, and the book’s broader implications for postcolonial and decolonial historiography.